2011
DOI: 10.1002/adma.201004306
|View full text |Cite
|
Sign up to set email alerts
|

High‐Performance Programmable Memory Devices Based on Co‐Doped BaTiO3

Abstract: Recently, resistive random access memory (RRAM) devices have attracted great attentions for a variety of advantages such as high-density, high-speed, low-power, and thus promising applications in next-generation nonvolatile memory technology. [1][2][3][4] The memory effect is realized through switching between high resistance state (HRS) and low resistance state (LRS), controlled by electric fi eld with either opposite polarity (bipolar) or different magnitude (unipolar). In understanding this resistive switch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
125
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(130 citation statements)
references
References 23 publications
4
125
0
1
Order By: Relevance
“…Until now RS was observed only in lithographically fabricated devices (MIM capacitors or transistors), the gate areas of which are covered by a metal film, which prevents a direct observation of the post-forming features of the dielectric material. 8,9 Therefore, a device-level study cannot unambiguously address the questions of (a) whether the switching is filament-driven and (b) which morphological properties of the dielectric can be responsible for the RS. In this study, the RS phenomenon in HfO 2 dielectric, in both the amorphous and polycrystalline phases, was studied at the nanoscale using conductive atomic force microscopy (CAFM).…”
mentioning
confidence: 99%
“…Until now RS was observed only in lithographically fabricated devices (MIM capacitors or transistors), the gate areas of which are covered by a metal film, which prevents a direct observation of the post-forming features of the dielectric material. 8,9 Therefore, a device-level study cannot unambiguously address the questions of (a) whether the switching is filament-driven and (b) which morphological properties of the dielectric can be responsible for the RS. In this study, the RS phenomenon in HfO 2 dielectric, in both the amorphous and polycrystalline phases, was studied at the nanoscale using conductive atomic force microscopy (CAFM).…”
mentioning
confidence: 99%
“…[26][27][28][29][30] Li et al 31 and Chang et al 28 reported the BRS behavior in the multilayer BTO thin film with a very high compliance current ∼ 100 mA. Similarly, Yan et al 32 reported URS behavior in the Co doped BTO thin films with a compliance current ∼ 100 mA. In addition, Chang et al reported an ON/OFF ratio study with varying top electrodes such as Al, ITO, Au and Pt; where it shows that Au and Pt as top metal electrodes offer the R off /R on ratio ∼10.…”
Section: © 2017 Author(s) All Article Content Except Where Otherwismentioning
confidence: 99%
“…More interestingly, the resistive switching occurs at bias as low as 1 V, without a forming process by large voltage, which is usually required by most resistive switching system. [12][13][14] This is very promising for RRAM memories with ultralow operation bias.…”
Section: -2mentioning
confidence: 99%